In Silico Identification of Chalcone-Imine Hybrids as a Promising Ptpn11 Inhibitors: An Integrated Network Pharmacology, Docking and ADMET Study (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Breast cancer is one of the most prevalent malignancies and a leading cause of cancer- related deaths among women. Although considerable progress has been made in diagnosis and treatment, the development of drug resistance and metastasis remains a significant therapeutic challenge. Targeting oncogenic signaling proteins such as tyrosine-protein phosphatase non-receptor type 11 (PTPN11) has emerged as a promising strategy for the development of effective anticancer therapies. In the present study, fifteen chalcone-imine hybrids have been designed. Network pharmacology approach was employed to identifying top targets. The overlapping targets were subjected to protein-protein interaction (PPI) analysis using the STRING database, followed by hub gene identification through Cytoscape software, and revealed that the compounds may exert their anti-breast cancer effects by modulating key breast cancer-related signaling pathways. Survival analysis was performed using the GEPIA database and the expression analysis revealed that PTPN11 as a promising therapeutic target. To validate these findings, molecular docking was carried out against selected target proteins, and the binding affinities and interaction profiles were compared with those of co-crystallized ligands and standard anticancer drugs. The results revealed that all the designed compounds have pronounced activity against PTPN11. In conclusion, these findings suggest that chalcone-imine hybrids represent promising candidates for anti-breast cancer drug development.
Keywords: Chalcone-imine hybrids; Network Pharmacology; Breast Cancer; Molecular Docking